The Significance of Teaching Peace to Multinational and Multicultural Student Groups - Jednaszewski, Piotr (International Transitions, 2025)
This article highlights the growing importance of peace education in a globalized world, characterized by increasingly multi-ethnic and multicultural societies. In the face of challenges such as migration, armed conflicts, religious tensions, nationalism, postcolonial injustices, environmental crises, and digital misinformation, peace edu-cation emerges as a fundamental tool for promoting understanding, tolerance, and social cohesion. The implementation of such education plays a key role in countering hate speech, prejudice, radicalization, and discrimination. It must incorporate new dimensions such as digital communication, environmental sustainability, and economic justice. However, its integration into educational systems remains limited, often overshadowed by economic and technological priorities. The article thus advocates for a renewed emphasis on peace education, particularly for students from diverse cultural backgrounds, as a means to build a more equitable, empathetic, and peaceful society.